Work engagement as a central driver: Reassessing employee well-being metrics and performance - Ratna Rosalina, Luh; Rahmawati, Putu Indah; Sinarwati, Ni Kadek (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
Traditional metrics of employee well-being, such as satisfaction and commitment, are now under scrutiny by scholars. There's growing concern that these measures might lead to complacency rather than maximizing workforce potential. Amidst this debate, work engagement is highlighted as a crucial determinant in enhancing workforce performance, especially in ever-evolving work contexts. This study aims to bridge existing gaps by unearthing the intricate relationships between work engagement, job satisfaction, and performance in the public sector. Data for the study were gathered through a survey questionnaire administered to 538 civil servants employed in the Indonesian government sector. Thus, the proposed mediation model was evaluated using Sobel test. The results revealed that work engagement does affect employee performance both directly and indirectly through job satisfaction. Intriguingly, the direct effect of work engagement on performance proved more dominant, marking it as a central contributor to productivity and efficacy in the public realm. This elucidates a complex interplay, emphasizing that while satisfaction plays a role, it's the intrinsic engagement of employees that stands paramount in driving optimal outcomes in the public sector.